PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM MELAKUKAN TRANSAKSI PEMBELIAN SECARA ONLINE - Moh Anwar; Moh. Kurdi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
Online transactions are buying and selling behavior carried out online by buyers and sellers which are not carried out face-to-face directly but through internet media. The problem in this research is about the role of law in consumer protection. According to the Consumer Protection Law no. 8 of 1999 is a legal product that can provide legal protection to consumers in conducting online transactions. The role of law in consumer protection can be seen from the perspective of public law and private law. The enactment of the Electronic Information Transaction Law Number 11 (UU ITE) of 2008 seems to be a solution to protect consumers.